2019
DOI: 10.1124/jpet.119.260059
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Phosphodiesterase 9A Inhibitor BI 409306 Increases Cyclic Guanosine Monophosphate Levels in the Brain, Promotes Synaptic Plasticity, and Enhances Memory Function in Rodents

Abstract: N-methyl-D-aspartate (NMDA) receptor-dependent long-term potentiation (LTP) is an established cellular model underlying learning and memory, and involves intracellular signaling mediated by the second messenger cyclic guanosine monophosphate (cGMP). As phosphodiesterase (PDE)9A selectively hydrolyses cGMP in areas of the brain related to cognition, PDE9A inhibitors may improve cognitive function by enhancing NMDA receptor-dependent LTP. This study aimed to pharmacologically characterize BI 409306, a novel PDE9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…As mentioned above, cGMP, a well‐known second messenger, by activating PKG takes part in both early‐ and late‐LTP, which are generally recognized as the electrophysiological correlates of short‐ and long‐term memory, respectively. Indeed, selective inhibitors of cGMP‐degrading enzymes, such as PDE5 and PDE9, have been consistently reported to enhance LTP, learning and memory formation/consolidation under physiological and pathological conditions 25,26 . Intriguingly enough, in senescence‐accelerated and AD mice models, the selective PDE5 inhibitors, sildenafil and tadalafil, were shown to reduce PHF and to rescue memory dysfunctions 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, cGMP, a well‐known second messenger, by activating PKG takes part in both early‐ and late‐LTP, which are generally recognized as the electrophysiological correlates of short‐ and long‐term memory, respectively. Indeed, selective inhibitors of cGMP‐degrading enzymes, such as PDE5 and PDE9, have been consistently reported to enhance LTP, learning and memory formation/consolidation under physiological and pathological conditions 25,26 . Intriguingly enough, in senescence‐accelerated and AD mice models, the selective PDE5 inhibitors, sildenafil and tadalafil, were shown to reduce PHF and to rescue memory dysfunctions 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…The promising results of in vitro and in vivo studies, and the growing interest of major pharmaceutical companies, encourage medicinal chemists to explore the field of selective PDE9 inhibitors as a novel approach against dementia [18,40]. Synthetic PDE9 inhibitors are indeed currently being investigated in clinical trials as promising therapeutic options against neurodegeneration [41].…”
Section: Natural and Nature-inspired Pde9 Inhibitorsmentioning
confidence: 99%
“…PDE9 is among the currently most studied innovative targets for developing inhibitors to combat dementia [5,18], in light of its expression in the brain and of its unique structural features that allow the design of molecules selectively interacting with this target, as will be discussed in the following. PDE9 is endowed with high affinity for cGMP (K m = 70 nM) and the highest selectivity over cAMP (K m = 230 µM) among the other isoforms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Following oral dosing with BI 409306 0.5 mg/kg via MDA [25], pharmacokinetic analysis in mice indicated that maximal plasma concentration of BI 409306 was reached within 30 min, with a mean (standard deviation [SD]) plasma concentration of 270 (65) nM (Supplementary Table S3). Based on the potency of BI 409306 against the PDE9 enzyme and a CSF/plasma ratio of 0.2 [7], this plasma exposure corresponds to a CSF exposure similar to the BI 409306 half maximal inhibitory concentration (IC 50 ) against PDE9. Furthermore, this plasma exposure was in the range reported in clinical studies in healthy male volunteers and in patients with schizophrenia after a single oral dose of BI 409306 25 mg [8,29].…”
Section: Pharmacokinetic Study and Plasma Exposurementioning
confidence: 99%
“…BI 409306 is a novel PDE9 inhibitor, a class of compounds that are thought to promote NMDA receptor-related glutamatergic transmission by elevating postsynaptic levels of cGMP in neurons [4,5]. In rodents, BI 409306 has been shown to increase cGMP in brain tissue and cerebrospinal fluid (CSF), promote synaptic plasticity (evaluated using hippocampal long-term potentiation), improve episodic memory, and reverse working memory deficits induced by acute pharmacological blockade of NMDA receptors [7]. Furthermore, dose-dependent increases in cGMP levels in the CSF of healthy volunteers have been observed after a single oral dose of BI 409306 [8].…”
Section: Introductionmentioning
confidence: 99%